AB0202 The increasing use of ultrasonography to guide corticosteroid injections. (1st June 2001) - Brown, AK; Karim, Z; Quinn, MA; Wakefield, RW; Conaghan, PG; O'Connor, P; Emery, P
Abstract : Background: Local corticosteroid injection is a standard treatment for joint and soft tissue inflammation. However, these injections are often inaccurately placed and this can affect clinical outcome. Ultrasonography (US) has the ability to precisely identify local pathology, thereby improving diagnosis and is also able to accurately guide placement of corticosteroid injections. In our unit, a dedicated rheumatology US machine is available in the out-patient department operated by experienced rheumatology research fellows trained in musculoskeletal US. Objectives: To evaluate the number, site and indication for US-guided soft tissue and intra-articular corticosteroid injection compared with the standard 'blind' clinical approach. Methods: Consecutive patients receiving soft tissue and intra-articular corticosteroid injection in the rheumatology out-patient clinics at Leeds General Infirmary over a two-week period were included in this observational study. Information recorded on a standard case report form included patient details, injection site, indication for injection and whether patients received a standard or an US-guided injection. Results: Overall, 91 patients received 127 soft tissue and intra-articular corticosteroid injections. 17 patients (19%) were referred for an US-guided procedure and these patients received 26 injections (20% of total injections). The sites injected using US were small joints of the hands and feet (8), tendon sheaths (8), shoulder (4), hip (3), wrist (2) and sternoclavicular joint (1). Seven patients referred for US-guided corticosteroid injection (41%) reported a poor response to a previous standard injection. US was used to confirm the local diagnosis in 6 patients (35%) before a guided injection was performed. Conclusion: The use of US to guide corticosteroid injections is increasing, especially in patients who have failed to respond to a standard injection. US is particularly useful when clinical diagnosis is uncertain or injection is technically difficult. As US becomes increasingly used in rheumatological practise, more rheumatologists may wish to learn the technique of US-guided injection which will require training. Further work is required to determine whether US-guided corticosteroid injection is of additional benefit to patients. References: Karim Z, Wakefield RJ, Lawson C, et al . The impact of ultrasonography on the diagnosis and management of patients with musculoskeletal conditions. Arthritis Rheum. 2000;43:S299 Cicak N, Matasovic T, Bajraktarevic T. Ultrasonographic guidance of needle placement for shoulder arthrography. J Ultrasound Med. 1992;11:135–7 Jones A, Regan M, Ledingham J, et al . Importance of placement of intra-articular steroid injections. BMJ 1993;307:1329–30 Eustace JA, Brophy DP, Gibney RP, et al . Comparison of the accuracy of steroid placement with clinical outcome in patients with shoulder symptoms. Ann Rheum Dis. 1997;56:59–63